Noninvasive Measurement of Humidity Distribution in Polymer Electrolyte Fuel Cells (PEFCs). Part II: Operando Analysis of a Fuel Cell Stack. Issue 12 (1st December 2022) - Schuller, A.; Schmidt, T. J.; Eller, J.
Abstract : In the second part of the paper series on a noninvasive method to determine the local high frequency resistance (HFR) distribution in polymer electrolyte fuel cells (PEFC), the method is applied to an operating PEFC stack. While in the first part of this paper series the approach of using multiple surface attached electrodes to locally inject 1 kHz AC currents into a cell and to measure the resulting voltage amplitudes at the flow field's surface was introduced. Its sensitivity was assessed using a stack fed only by nitrogen at different humidification levels. Here, it is confirmed that the approach works also during electrochemical operation. First, the method's spatial resolution is further explored and improved by using multiple stimulation patterns after examining the local sensitivity of the different electrode combinations to changes in membrane conductivity by finite element model simulations of the current injection. The method is then applied to a stack operated at different current densities, inlet humidities and gas flow configurations. The HFR distributions are in good agreement with literature data and compare well with the global cell HFR. Finally, the method's transient capabilities are highlighted by measuring the HFR distribution during a current jump and cell drying.